(untitled) (KULT_online, 2025)
The edited volume Widerspruchs-Kulturen: Medien, Praktiken und Räume des Widersprechens offers an interdisciplinary analysis of contemporary practices of contradiction. In three sections, the authors examine social, artistic and academic perspectives on contradiction as a practice. Despite some minor ambiguities, the volume offers a differentiated examination of normative tensions and is particularly enriching for young cultural and social scientists.